L’évolution du droit des assurances : aspects constitutionnels et législatifs - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1982)
In his article, Mr. Rémi Moreau conveys a two-tiered aspect of insurance law. On one level, he exposes with whom lies the legislative power to regulate the industry. This the author illustrates through the citing of a number of disagreements having arisen between the federal and provincial governments. On another level, Mr. Moreau reviews the various laws respecting insurance in Québec and the major reforms carried out in recent years, more especially the 1974 amending of The Insurance Act and the introduction in 1977 of The Automobile Insurance Act.